Comparative analyses of SPI and SPEI as drought characterization tools in Massili watershed, central Burkina Faso - Bontogho, Tog-Noma Patricia Emma; Kansole, Michelline Marie Regina; Kabore, Mamounata; Guira, Moussa (International Journal of Hydrology Research, 2023)
Assessment of hydrological drought indices in drought prone areas provides useful information for accurate and sustainable water resources management. However, meteorological drought estimation in ungauged basin remains less studied. The main objective of this study was to compare the ability of Standardized Precipitation Index (SPI) and Standardized Precipitation Evapotranspiration Index (SPEI) to reproduce historiological drought within Massili basin. To this end, monthly historical rainfall and temperature time series spanning from 1960 to 2021 have been collected from the national agency of meteorology. R programming language has been applied to display Boxplots in order to identified the temporal dispersion of the rainfall indices. Then the Spearman correlation was applied to illustrate the relationships between the SPEI and the SPI. The results shows that both SPEI and SPI exhibit consistent behavior in observed drought within the Massili watershed. Dry conditions prevailed during the period 1980–1990, 1990–2000 and 2000-2010. Severe wet conditions prevailed in years 1984, 1985,1998 and 2002. In all time scale the SPEI and SPI are characterized by high correlation. The Spearman correlation coefficients value is above 0.7 with the highest correlation value detected between SPEI-24 and SPI-24 (0.97). This study may contribute to better understand the drought patterns within the basin for water resources planning perspectives.